905 Improving Confidence in Plastering Across Specialties: A Hands-on Approach. (19th August 2022) - Sambhwani, S; Baba, M; Hirschowitz, D; Shrestha, S; Khairandish, H
Abstract: Aim: Plaster of Paris casts form one the most basic yet effective treatment for acute orthopaedic fractures and often form a permanent treatment methodology. Patients with fractures present at all times of the day to acute services and require prompt stabilisation. Casts however do present some risks including compartment syndrome and skin ulcerations. Our quality improvement aimed to improve confidence in healthcare providers across different specialities in managing plasters. Method: Focussed workshops conducted by expert plaster technicians under the supervision of an experienced orthopaedic consultant were conducted for upper and lower limb injuries. Additional workshops encompassing plaster safety and other trauma splints were delivered. Candidates ranged across different grades and included nurse practitioners and qualified doctors. Confidence scores (out of five) measured on a Likert scale were obtained from 25 participants. Results: Knowledge about plasters including type of plaster matched to injury improved from a mean score of 3 to 4.5. Confidence in applying upper limb plasters improved from a mean score 3 to 4.7 and applying lower limb plasters improved from a mean score of 3.25 to 4.8. Confidence in plaster safety including acute conditions and safe removal improved from a mean score of 2 to 4.6. Confidence in applying acute splints improved from a mean score of 1.5 to 4.3. Conclusions: Our quality improvement project improve the confidence in practitioners managing acute orthopaedic patients with an emphasis on plaster safety and acute splints. It has been formally adopted on a regular basis as a teaching program.